Physical activity measurement in persons with chronic and disabling conditions: methods, strategies, and issues. - Warms, Catherine (Family & Community Health)
Measuring the physical activity of persons with chronic and disabling conditions presents complexities related to measuring instruments, the intensity of the activity being measured, the population being measured, and individual behavior and health status. They often have limitations in mobility that do not preclude physical activity but contribute to the complexity of measuring it, such as slow or altered gait, inability to walk, and the need for assistive devices. This article reviews currently available ways to measure physical activity, describes strengths and weaknesses of various measures, and provides examples of complexities in measuring physical activity in people who move differently.